Polar kya in Urdu: Both Mirative and Interrogative - Hussain, Jabir; Sharif, Ahmad Naveed (Pakistan Languages and Humanities Review, 2023)
This study aims to address the following question: what are the licensing conditions for the Urdu/Hindi polar question particle kya’s multiple concept selection behaviour? More specifically, what is the nature of contexts in which kya contributes both interrogative and mirative meanings, and how can such a phenomenon be characterized in terms of cognitive semantic compositional processes? To address this research question, the present study uses the Lexical Concept and Cognitive Model (Evans, 2009) as its theoretical underpinnings. This framework proposes the constructs of Lexical Concept and Cognitive Model to account for the mechanisms of semantic composition for polyfunctional phenomena. The study employs multiple data sources such as naturally occurring data, individual and dialogical introspections and Urdu Lughat. The study finds that to encode interrogative as well as mirative meanings, the polar kya undergoes the semantic compositional processes of lexical concept selection, integration and interpretation for final information characterization. The study concludes that kya can encode multiple lexical concepts in certain contexts, and its pragmatic functions result from construal imposed on the propositional content in the prior discourse. Theoretically the study shows that linguistic form-meaning relation is shaped by actual use.